Attentional Resources Are Needed for Auditory Stream Segregation in Aging - Dinces, Elizabeth; Sussman, Elyse S. (Frontiers in Aging Neuroscience, 2017)
The ability to select sound streams from background noise becomes challenging with age, even with normal peripheral auditory functioning. Reduced stream segregation ability has been reported in older compared to younger adults. However, the reason why there is a difference is still unknown. The current study investigated the hypothesis that automatic sound processing is impaired with aging, which then contributes to difficulty actively selecting subsets of sounds in noisy environments. We presented a simple intensity oddball sequence in various conditions with irrelevant background sounds while recording EEG. The ability to detect the oddball tones was dependent on the ability to automatically or actively segregate the sounds to frequency streams. Listeners were able to actively segregate sounds to perform the loudness detection task, but there was no indication of automatic segregation of background sounds while watching a movie. Thus, our results indicate impaired automatic processes in aging that may explain more effortful listening, and that tax attentional systems when selecting sound streams in noisy environments.